The 2nd Czech and Polish Conference on Number Theory Cieszyn 1998. Problem session - AMSil, Redakcja (Annales Mathematicae Silesianae, 1998)
The 2nd Czech and Polish Conference on Number Theory Cieszyn 1998. Problem session.